The Effect Of Digital Leadership on Motivation, Engagement, And Employee Performance Using Social Network Analysis Method: Evidence From The Largest Highway Tollroad in Indonesia (Infrastructure Company) - Rr. Hernitasari A; Mone S. Andrias (Syntax Corporation, 2022)
The existence of the Covid-19 pandemic has an impact on accelerating digitalization or digital transformation. This impact forces the use of technology more massively and becomes a big challenge for several companies. The study will be conducted at one of Indonesia's largest toll road companies, which was affected by digital transformation. Companies that adopt digital leadership are considered to perform better. Leadership practices have evolved to adapt to this changing landscape with the increasing adoption of digital technologies in the workplace. This study utilizes SNA to investigate the relationship between digital leadership and employee motivation, engagement, and performance. The findings reveal that digital leadership positively influences employee motivation and engagement, improving employee performance. Specifically, leaders who demonstrate effective digital leadership behaviours such as leveraging technology, promoting digital collaboration, and fostering a digital culture are more likely to have motivated, engaged, and high-performing employees. These findings contribute to understanding how digital leadership impacts employee outcomes in companies. The implications of this research suggest that organizations should invest in developing digital leadership capabilities among their leaders to enhance employee motivation, engagement, and performance in the digital era. This study also highlights the importance of leveraging SNA as a valuable research method to examine leadership dynamics in the digital workplace.